Artemisia herba-alba essential oil from Buseirah (South Jordan): Chemical characterization and assessment of safe antifungal and anti-inflammatory doses. (4th November 2015) - Abu-Darwish, M.S.; Cabral, C.; Gonçalves, M.J.; Cavaleiro, C.; Cruz, M.T.; Efferth, T.; Salgueiro, L.
Abstract: Ethnopharmacologic relevance: Artemisia herba-alba Asso ("desert wormwood" in English; "armoise blanche" in French; "shaih" in Arabic), is a medicinal and strongly aromatic plant widely used in traditional medicine by many cultures since ancient times. It is used to treat inflammatory disorders (colds, coughing, bronchitis, diarrhea), infectious diseases (skin diseases, scabies, syphilis) and others (diabetes, neuralgias). In Jordanian traditional medicine, this plant is used as antiseptic and against skin diseases, scabies, syphilis, fever as well as menstrual and nervous disorders. Aim of the study: Considering the traditional medicinal uses and the lack of scientific studies addressing the cellular and molecular players involved in these biological activities, the present study was designed to unveil the antifungal and anti-inflammatory activities of A. herba-alba Asso essential oil at doses devoid of toxicity to mammalian cells. Materials and methods: Chemical analysis of A. herba-alba essential oil isolated by hydrodistillation from aerial parts was carried out by gas chromatography (GC) and gas chromatography–mass spectrometry (GC–MS). The antifungal activity (minimal inhibitory concentrations and minimal lethal concentrations) was evaluated against yeasts, dermatophyte and Aspergillus strains. In order to explore the mechanisms behind the anti-fungal effect of the essential oil, the germ tube inhibition assay was evaluated using Candida albicans . The assessment of cell viability was accomplished using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and the in vitro anti-inflammatory potential of A. herba-alba oil at the periphery and central nervous system was evaluated by measuring nitric oxide (NO) production using lipopolysaccharide (LPS)-stimulated mouse macrophages and microglia, respectively. Results: Oxygen-containing monoterpenes are the main compounds of the oil, namely 1, 8-cineole (20.1%), β-thujone (25.1%), α-thujone (22.9%) and camphor (10.5%). Among the fungal strains tested, the oil demonstrated potential against Trichophyton rubrum and Epidermophyton floccosum, with minimal inhibitory concentration (MIC) and minimal lethal concentration (MCL) values of 0.32 mg/mL and Cryptococcus neoformans with MIC of 0.64 mg/mL. The oil revealed a strong inhibitory effect on germ tube formation in C. albicans with inhibition of filamentation around 90% at a concentration 0.16 mg/mL. Importantly, the essential oil significantly inhibited NO production evoked by LPS without cytotoxicity at concentrations up to 1.25 µL/mL in macrophages and up to 0.32 µL/mL in microglia. Furthermore, evaluation of cell viability in RAW 264.7 macrophages, BW2 microgliacells and HaCaT keratinocytes showed no cytotoxicity at concentrations up to 0.32 μL/mL. Conclusions: It was possible to find appropriate doses of A. herba-alba oil with both antifungal and anti-inflammatory activities and without detrimental effects towards several mammalian cell types. These findings add significant information to the pharmacological activity of A. herba-alba essential oil, specifically to its antifungal and anti-inflammatory therapeutic value, thus justifying and reinforcing the use of this plant in traditional medicine. Graphical abstract: